2016
DOI: 10.1073/pnas.1522730113
|View full text |Cite
|
Sign up to set email alerts
|

Distinct oligoclonal band antibodies in multiple sclerosis recognize ubiquitous self-proteins

Abstract: Oligoclonal Ig bands (OCBs) of the cerebrospinal fluid are a hallmark of multiple sclerosis (MS), a disabling inflammatory disease of the central nervous system (CNS). OCBs are locally produced by clonally expanded antigen-experienced B cells and therefore are believed to hold an important clue to the pathogenesis. However, their target antigens have remained unknown, mainly because it was thus far not possible to isolate distinct OCBs against a background of polyclonal antibodies. To overcome this obstacle, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
114
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 46 publications
7
114
1
Order By: Relevance
“…There is one clear limitation to the study by Brändle et al (4). Although they generated six OCB rAbs from four MS patients, they were successful in identifying the specificity of only three antibodies originating from two patients.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…There is one clear limitation to the study by Brändle et al (4). Although they generated six OCB rAbs from four MS patients, they were successful in identifying the specificity of only three antibodies originating from two patients.…”
mentioning
confidence: 98%
“…Identification of those antigens recognized by OCB antibodies is thought to hold fundamental clues to the pathogenesis of MS. In a recent PNAS publication, Brändle et al (4) provide evidence that OCB in MS target ubiquitous intracellular antigens released in cellular debris.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by others [13] demonstrated that antibodies contributing to the oligoclonal banding observed in MS patients are directed against ubiquitous intracellular proteins. However, eleven of the rhAbs we tested are brain-specific by ELISA (Brain+ Kidney- Flu- OVA-) and fourteen of the rhAbs we tested are brain-specific by ICC (Sy5y+ Hep-2-).…”
Section: Discussionmentioning
confidence: 99%
“…Wekerle and colleagues screened recombinant cerebrospinal fluid oligoclonal immunoglobulin bands for binding to antigen libraries. They noted binding to a set of intracellular structures that hardly qualify as classic demyelinating antibody candidates (26). On the other hand, Alexander Gabibov (Russian Academy of Sciences, Moscow) reported that one of the main MS autoantigens, myelin basic protein, escapes ubiquitination control for proteasomal degradation.…”
Section: Therapeutic Avenuesmentioning
confidence: 99%